Analisis Asrama Pesantren Al-Munawwir Krapyak Yogyakarta dalam Perspektif Pendisiplinan Tubuh Michael Foucault - Mustaqim; Rinaldi, Anugerah; Saputra, Dean Rizky (Jurnal Noken: Ilmu-Ilmu Sosial, 2024)
Pesantren is a very unique educational institution owned by Indonesia, therefore a multidimensional perspective is needed to discuss it. This is important to create a richer and more diverse discussion about pesantren. This research tries to examine the dormitory element as an important part of the pesantren, knowing how the system of applying rules in the pesantren dormitory in the perspective of Michael Foucault's body discipline theory. This research approach uses descriptive qualitative with data collection techniques in various sources, direct observation, and interviews, trying to explore various data both primary and secondary data. The focus of this research is to see how the application of rules in Al-Munawwir Krapyak Yogyakarta boarding school for its students in order to form a disciplined character seen from the body discipline approach. The results of this study show that there are many things that are relevant in the application of the rules in Al-Munawwir Krapyak Yogyakarta boarding school with the study of body discipline from Michael Foucault